2006
DOI: 10.2224/sbp.2006.34.8.927
|View full text |Cite
|
Sign up to set email alerts
|

Body Image and Personality Traits of Male-to-Female Transsexuals and Homosexuals

Abstract: The aim of this study is to identify the body image and personality traits of male-to-female transsexual and homosexual persons in Turkey: 36 homosexuals and 52 male-to-female transsexuals were evaluated. According to the Body Cathexis Scale (Secord & Jourard, 1953) transsexuals compared with controls are statistically more satisfied with their waist, height, eyes, hips, legs, body posture and weight; dissatisfied with their body hair distribution, shoulder width and genitals. Homosexuals compared with co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 15 publications
1
15
1
Order By: Relevance
“…They concluded that whist sexual reassignment (i.e., hormones and/or Sex Reassignment Surgery; SRS) may increase body satisfaction for a trans person, enhancing body image should also take a more holistic stance, paying more attention to the psychological component of body image. In contrast to these findings, Bozkurt et al (2006) found that although there was some difference in body satisfaction with some parts of the body, body satisfaction did not significantly differ in homosexual people (n=36), trans females (n=52), and aged matched heterosexual cisgender people (n=72). They concluded that trans people experience similar levels of body dissatisfaction in comparison to homosexual and cisgender people.…”
Section: Body Dissatisfaction In Trans People: Review Of the Studiescontrasting
confidence: 63%
See 4 more Smart Citations
“…They concluded that whist sexual reassignment (i.e., hormones and/or Sex Reassignment Surgery; SRS) may increase body satisfaction for a trans person, enhancing body image should also take a more holistic stance, paying more attention to the psychological component of body image. In contrast to these findings, Bozkurt et al (2006) found that although there was some difference in body satisfaction with some parts of the body, body satisfaction did not significantly differ in homosexual people (n=36), trans females (n=52), and aged matched heterosexual cisgender people (n=72). They concluded that trans people experience similar levels of body dissatisfaction in comparison to homosexual and cisgender people.…”
Section: Body Dissatisfaction In Trans People: Review Of the Studiescontrasting
confidence: 63%
“…Out of the 26 papers which met the criteria for inclusion in this review, 18 explored the prevalence of body image in a trans population Becker et al, 2015;Bozkurt et al, 2006;Colizzi et al, 2015;De Vries et al, 2011Fisher et al, 2013Fisher et al, , 2014Fleming, MacGowan, Robinson, Spitz, & Salt, 1982;Kozee, Tylka, & Bauerband, 2012;Kraemer, Delsignore, Schnyder, & Hepp, 2007;Lai, Chiu, Gadow, Gau, & Hwu, 2010;Lindgren & Pauly, 1975;Marone, Lacoella, Cecchini & Ravenna, 1998;Pauly & Lindgren, 1976;Smith, Van Goozen, Kuiper, & Cohen-Kettenis, 2005;Steensma, McGuire, Kreukels, Beekman, & Cohen-Kettenis, 2013;Wolfradt & Neumann, 2001). Three studies explored disordered eating in trans individuals (Ålgars et al, 2012;Khoosal, Langham, Palmer, Terry, & Minajagi, 2009;Silverstein, Carpman, Perlick, & Perdue, 1990).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations